2007
DOI: 10.1021/jf063423e
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Reactivity Relationships of Flavan-3-ols on Product Generation in Aqueous Glucose/Glycine Model Systems

Abstract: Ring structure-reactivity relationships of three flavan-3-ols [epicatechin (EC), epicatechin gallate (ECG), and epigallocatechin gallate (EGCG)] and three simple phenolic compounds (1,3,5-trihydroxybenzene, 1,2,3-trihydroxybenzene, and methylgallate as the analogous individual A, B, and C benzene rings of EGCG) on product generation in an aqueous glucose-glycine reaction model system (125 degrees C and 30 min) were investigated. The addition of EC, ECG, or EGCG to a glucose-glycine model was reported to simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 14 publications
6
44
0
Order By: Relevance
“…A similar carbonyl-trapping property can be attributed to epicatechin gallate, which has also been reported to form adducts with dicarbonyls in model systems (Lo et al, 2006;Noda & Peterson, 2007). The only structural difference between the two flavan-3-ols is located in the Studies in glucose/glycine model systems with added ferulic acid showed that it can undergo decarboxylation, exposing the vinyl group, which could, in turn, undergo various pericyclic reactions with Maillard intermediates (in low moisture conditions) or form adducts with C 2 and C 3 sugar fragments, by electrophilic aromatic substitution reactions (in aqueous model systems) (Jiang, et al, 2009).…”
Section: Acrylamide Formation In Asparagine-glyoxal Model Systems Witsupporting
confidence: 53%
“…A similar carbonyl-trapping property can be attributed to epicatechin gallate, which has also been reported to form adducts with dicarbonyls in model systems (Lo et al, 2006;Noda & Peterson, 2007). The only structural difference between the two flavan-3-ols is located in the Studies in glucose/glycine model systems with added ferulic acid showed that it can undergo decarboxylation, exposing the vinyl group, which could, in turn, undergo various pericyclic reactions with Maillard intermediates (in low moisture conditions) or form adducts with C 2 and C 3 sugar fragments, by electrophilic aromatic substitution reactions (in aqueous model systems) (Jiang, et al, 2009).…”
Section: Acrylamide Formation In Asparagine-glyoxal Model Systems Witsupporting
confidence: 53%
“…This reaction also involves ascorbic acid and phenolic degradation (Nicoli, Anese, & Parpinel, 1999). EC and EGCG have been demonstrated to reduce the extent of the Maillard reaction in a glucose-glycine model system (Noda & Peterson, 2007). Similar inhibition could have occurred in GT-fortified apple product.…”
Section: Resultsmentioning
confidence: 92%
“…Some phenolic extracts can inhibit these reactions (Rudnicki et al, 2007;Ho, Wu, Lin, & Tang, 2010;Tsuji-Naito, Saeki, & Hamano, 2009;. In an aqueous glucose/ glycine model system EC, ECG and EGCG were reported to inhibit glycation by acting through carbonyl trapping, which involves the A-ring (the meta-polyhydroxylated benzene ring) (Noda & Peterson, 2007). In a protein-glucose model system, Nakagawa, Yokozawa, Terasawa, Shu, and Juneja (2002) found that GT catechins containing a gallate moiety at the C-3 position of the C-ring (e.g.…”
Section: Tablementioning
confidence: 99%
“…Furthermore, flavonols (Noda and Peterson, 2007) and hydroxycinnamic acids (Jiang et al, 2009) have been shown to alter the progression of the Maillard reaction. Thus, there is an ever-expanding list of components that can be used to manipulate the Maillard reaction, and an understanding of the underlying mechanisms helps to direct the Maillard reaction in the desired direction.…”
Section: Interactions With Other Components Of the Foodmentioning
confidence: 99%